6x+a+2ax+3=(3+a)(2x+1)

Simple and best practice solution for 6x+a+2ax+3=(3+a)(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+a+2ax+3=(3+a)(2x+1) equation:


Simplifying
6x + a + 2ax + 3 = (3 + a)(2x + 1)

Reorder the terms:
3 + a + 2ax + 6x = (3 + a)(2x + 1)

Reorder the terms:
3 + a + 2ax + 6x = (3 + a)(1 + 2x)

Multiply (3 + a) * (1 + 2x)
3 + a + 2ax + 6x = (3(1 + 2x) + a(1 + 2x))
3 + a + 2ax + 6x = ((1 * 3 + 2x * 3) + a(1 + 2x))
3 + a + 2ax + 6x = ((3 + 6x) + a(1 + 2x))
3 + a + 2ax + 6x = (3 + 6x + (1 * a + 2x * a))
3 + a + 2ax + 6x = (3 + 6x + (1a + 2ax))

Reorder the terms:
3 + a + 2ax + 6x = (3 + 1a + 2ax + 6x)
3 + a + 2ax + 6x = (3 + 1a + 2ax + 6x)

Add '-3' to each side of the equation.
3 + a + 2ax + -3 + 6x = 3 + 1a + 2ax + -3 + 6x

Reorder the terms:
3 + -3 + a + 2ax + 6x = 3 + 1a + 2ax + -3 + 6x

Combine like terms: 3 + -3 = 0
0 + a + 2ax + 6x = 3 + 1a + 2ax + -3 + 6x
a + 2ax + 6x = 3 + 1a + 2ax + -3 + 6x

Reorder the terms:
a + 2ax + 6x = 3 + -3 + 1a + 2ax + 6x

Combine like terms: 3 + -3 = 0
a + 2ax + 6x = 0 + 1a + 2ax + 6x
a + 2ax + 6x = 1a + 2ax + 6x

Add '-2ax' to each side of the equation.
a + 2ax + -2ax + 6x = 1a + 2ax + -2ax + 6x

Combine like terms: 2ax + -2ax = 0
a + 0 + 6x = 1a + 2ax + -2ax + 6x
a + 6x = 1a + 2ax + -2ax + 6x

Combine like terms: 2ax + -2ax = 0
a + 6x = 1a + 0 + 6x
a + 6x = 1a + 6x

Add '-6x' to each side of the equation.
a + 6x + -6x = 1a + 6x + -6x

Combine like terms: 6x + -6x = 0
a + 0 = 1a + 6x + -6x
a = 1a + 6x + -6x

Combine like terms: 6x + -6x = 0
a = 1a + 0
a = 1a

Solving
a = 1a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1a' to each side of the equation.
a + -1a = 1a + -1a

Combine like terms: a + -1a = 0
0 = 1a + -1a

Combine like terms: 1a + -1a = 0
0 = 0

Simplifying
0 = 0

The solution to this equation could not be determined.

See similar equations:

| 5y+(-12y)=x | | 9x+45=-3(x-39) | | 22(134+x)=22(3x+550) | | 22(134+x)=11(3x+550) | | -8x-48=4x-24 | | h+-2= | | 3f+-12= | | 2p(p-3)+4= | | 24+4g= | | 4+35x=28x+7 | | 5t+30= | | -4+3x=-8+13x | | 5x+10=-67-6x | | 20-2x=5-7x | | 2x+8=-27-3x | | (50+x)-(35+x)=15 | | 3x(2k-1)=5x(k-4) | | 8+11x=-42+x | | 24x^2-10x-1= | | 4x+14=4(n+8) | | x+14=4(n+8) | | 4(x-3)+2(x+1)= | | 8h-13=67 | | 4(3t-4)-2=30 | | 7m-11=38 | | Log(x^2+3x+36)=1+log(x-3) | | 14b=2-2 | | 5(2x+6)=-18+2 | | -4x-16=2x-10 | | 0.50x+0.20(9.0-x)=35 | | 12x-24=-4x+88 | | (3-10x)(x+23)=0 |

Equations solver categories